Sertão Planaltino: cultura, religiosidade e política no cadinho da modernização (1950 - 1964) - MAGALHÃES, Luiz Ricardo (2010)
This is a work which narrates the problems of changes seen in the backcountry culture of the Central Brazil and, for this, it goes forward on the ethics domain that had presided these changes. We concern here about the impacts reflected in the cultural environment when an extreme transition was occurring. The observed facts were caused by the movements of construction of Brazil s new federal capital at territories belonging to three municipalities of Goiás: Planaltina, Luziânia e Formosa. Searching for the meanings inscribed in the acceleration of history, the hallmark of this movement, we focus the effort of reflection on the observed singularities. Facts such as the interruption and then resumption of a major regional popular party, the Folia do Divino Espírito Santo, have instigated this analysis. The point was not to stick to the party itself, an ethnographic work that has been contemplated by interesting researches, such as from Lara Santos de Amorim and Inês Zats, but to rescue the story that deals with the dramas experienced by the people of the hinterland, called here Planaltina (the concept of mining of Zoroastro Artiaga, an intellectual of Goiás) who, in a very personal way, developed their own responses before the demands of having to adapt himself to a reality submitted to the requirements of quick changes. In the context of transformations, which if viewed through the prism of culture, could be classified as overwhelming, was imposed to the locals the presence of an exuberant city that was a symbol of modernity. Brasília, in its symbolic dimension, was not only the greatest icon of architectural modernism in Brazil, but the representation of the long cherished desire of the running of the country for its inclusion in the club of so-called developed nations. Around the zero point of this invention, which a long time ago has been defined as ideal, the previous community life, which was often classified as nothing or almost nothing, was forced to articulate a profusion of new concepts brought by the changes. To work with the culture, we appealed to literary, journalistic and memories sources. We hope, therefore, to have collaborated to satisfy desires for this reflection could reach the only foreshadowed hinterland historical significance.